The timing and amount of vagus nerve stimulation during rehabilitative training affect post-stroke recovery of forelimb strength - Hays, Seth A. (2014)
Loss of upper arm strength after stroke is a leading cause of disability. Strategies that can enhance the benefits of rehabilitative training could improve motor function after stroke. Recent studies in a rat model of ischemic stroke demonstrate that vagus nerve stimulation (VNS) paired with rehabilitative training substantially improves recovery of forelimb strength compared to extensive rehabilitative training without VNS. Here we report that the timing and amount of stimulation affect the degree of forelimb strength recovery. Similar amounts of delayed VNS delivered two hours after daily rehabilitative training sessions resulted in significantly less improvement compared to VNS that is paired with identical rehabilitative training. Significantly less recovery also occurred when several-fold more VNS was delivered during rehabilitative training. Both delayed and additional VNS confer moderately improved recovery compared to extensive rehabilitative training without VNS, but fail to enhance recovery to the same degree as VNS that is timed to occur with successful movements. These findings confirm that VNS paired with rehabilitative training holds promise for restoring forelimb strength post-stroke and indicate that both the timing and amount of VNS should be optimized to maximize therapeutic benefits.